Network Performance of the JBoss Application Server - Benothman, Nabil; Clere, Jean-Frederic; Schiller, Eryk; Kropf, Peter; Maucherat, Remy (: IEEE, 2013)
JBoss Application Server (AS) uses java.io and the Apache Portable Runtime (APR) project to provide its HTTP connectors. Due to new features of upcoming specifications of the Java Enterprise Edition (Java EE), the existing connectors shall be replaced by modern non blocking Input/Outputs (I/Os). In this study, we review some modern I/O frameworks such as NIO.2 introduced by Java SE 7 and XNIO3 developed by JBoss. We compare their network performance by running a series of stress tests on client-server applications of limited functionality. As a result, we select NIO.2 as the most appropriate framework to specify and implement a new JBoss connector. Finally, we compare our newly implemented Java connector against the existing APR-based one by means of network performance measures.
, 2013